Factors associated with acute respiratory infection among under-five children at Muara Enim community health center: A cross-sectional study - Yeti Yuliati; Yulis Marita; Fera Meliyanti (Lentera Perawat, 2025)
Background: Acute Respiratory Infection (ARI) remains a major public health problem among under-five children and contributes significantly to morbidity and primary health care utilization. Household environmental and behavioral factors are known to increase the risk of ARI, particularly in areas with substandard housing conditions. Objective: This study aimed to analyze factors associated with Acute Respiratory Infection among under-five children in the working area of Muara Enim community Health Center. Methods: This study employed a quantitative cross-sectional design. The study population consisted of all mothers with under-five children aged 0–59 months in Kelurahan Tungkal, Muara Enim District, totaling 444 individuals. A total of 82 respondents were selected using random sampling. Data were collected through face-to-face interviews using a structured questionnaire assessing cigarette smoke exposure, mosquito coil use, housing density, and household ventilation. Data were analyzed using the Chi-square test with a significance level of 0.05. Results: The findings showed significant associations between cigarette smoke exposure (p = 0.000), mosquito coil use (p = 0.000), housing density (p = 0.000), household ventilation (p = 0.002), and the occurrence of Acute Respiratory Infection among under-five children. Children exposed to these risk factors had a higher proportion of ARI compared to those who were not exposed. Conclusion: Acute Respiratory Infection among under-five children is significantly associated with household environmental and behavioral factors. Strengthening community-based health education focusing on ARI prevention is recommended, particularly regarding smoking cessation inside the home, reduction of mosquito coil use, and improvement of healthy housing conditions. Intersectoral collaboration is essential to support sustainable household environmental improvements.